Процес інституціоналізації неурядових міжнародних організацій у світовій політиці - Ільницька, Уляна (Видавництво Львівської політехніки, 2013)
Досліджено процес інституціоналізації неурядових міжнародних організацій у світовій політиці та становлення їх як активних та впливових суб’єктів міжнародних відносин; розглянуто особливості функціонування перших неурядових організацій; висвітлено динаміку зростання кількості неурядових організацій, відображено активізацію їх діяльності та значний вплив на світовий політичний процес; висвітлено політико-правовий статус сучасних неурядових організацій як інститутів системи міжнародних відносин. The article examines the process of institutionalization of non-governmental organizations in the world politics and the formation of both active and influential actors in international relations, as well as the specifics of functioning of the first non-governmental organizations. The article also gives a comprehensive account of growth dynamics of nongovernmental organizations, describes the revitalization of their activities and shows their significant impact on the global political processes. There is also an overview of the political and legal status of modern non-governmental organizations as entities of the international relations landscape.
Process of institutionalization of non-governmental organizations in world politics
Keywords: неурядові міжнародні організації; процес інституціоналізації неурядових міжнародних організацій; функціонування перших неурядових міжнародних організацій; особливості правосуб’єктності неурядових організацій у світовій політиці; non-governmental organizations; process of institutionalization of nongovernmental organizations; functioning of the first non-governmental international organizations; international and legal subjectivity of non-governmental organizations in world politics